The Potential of Empty Fruit Bunch (EFB) as Artificial Bait for Subteranean Termite: Pisoptera - Abdul Syukor, Abd Razak; Suryati, Sulaiman (Sila Science, 2014)
This study is to create effective artificial bait for termite using empty fruit bunches (EFB) with additional active ingredient (Imidacloprid). For in-situ experiment, there are two experiments. For the first experiment of different concentrations with and without skin, the concentrations used are 0.2%, 0.4%, 0.6%, 0.8% and 1.0% and control with moisture content of 65%. EFB fiber is soaked into the solution and oven-dried in 100°C for an hour. The samples are placed at the sampling houses. For the second experiment of different concentrations with and without skin, the concentrations used are 0.001% and 0.01% and control with moisture content of 65%. It then was oven-dried in 100°C for an hour. Result from that, there was no successfully result shown for the two experiments. For laboratory experiment, there are two experiments. For the soaking method with and without skin, the EFB fiber soaked into the Imidacloprid solution with 0.001%, 0.005% and 0.01% and control for 15 minutes with EFB with and without skin condition. EFB fiber is air-dried until the moisture content is 65%. 10 termites are placed into the sample. The suitable results are 0.001% and 0.005% with condition of EFB fiber with skin. For spraying method with and without skin, EFB fiber sprayed in Imidacloprid solution of 0.001%, 0.005%, 0.01% and air-dried until moisture content is 65%. 10 termites are also placed in the samples. The result is 0.005% of EFB fiber with skin condition. Microscopic analysis use electron microscope with camera PAXcam ARC, magnifical 40 xs and resolution 1280 x 1024. It shows that the dyed Imidacloprid had soaked into the EFB fiber thoroughly. From the comparison of the result, it concludes that the result used is 0.005% in the condition of EFB with skin by using spraying method.